Children’s Dietary Quality and Micronutrient Adequacy by Food Security in the Household and among Household Children - Shinyoung Jun (Nutrients, 2019)
Children’s food-security status has been described largely based on either the classification of food security in the household or among household children, but few studies have investigated the relationship between food security among household children and overall dietary quality. Our goal was to examine children’s dietary quality and micronutrient adequacy by food-security classification for the household and among household children. Data from 5540 children (2−17 years) from the National Health and Nutrition Examination Survey (NHANES) 2011−2014 were analyzed. Food-security status was assessed using the U.S. Household Food Security Survey Module and categorized into high, marginal, low, and very low food security for the households and among household children. Dietary quality and micronutrient adequacy were characterized by the Healthy Eating Index (HEI) 2015 and Mean Adequacy Ratio (MAR; based on total nutrient intakes from diet and dietary supplements), respectively. The HEI 2015 scores did not substantially vary by either food-security classification, but the MAR was greater in high compared to very low food security in households and among household children; a linear relationship was found only among household children. In general, very good agreement was observed between the classifications, but the strength of agreement differed by children’s age, race/Hispanic origin, and family income. In conclusion, micronutrient adequacy, but not dietary quality, significantly differed by food-security status. While the agreement between food security in the household and among household children is very good, classification of food security among household children may be more sensitive to detecting differences in exposure to nutrients.